The influence of donor bodies on the priorities of Public Administration in the Maghreb region:framing or guidance (قضايا سياسية, 2024)
The terrifying consequences of structural adjustment applications have not prevented drawing lessons learned from the danger of complying with the conditions of international financial institutions, as the literal commitment of the Maghreb countries to the "teachings" of these institutions has not helped to overcome the chronic malfunctions of Public Administration. The study aims to highlight the contexts of the development of the relationship of the Maghreb countries with the international financial institutions and their fate, based on the descriptive analytical approach in order to monitor the mechanisms of influence of donors in rearranging the priorities of Public Management, and to indicate the nature of the effects on public policies in the countries under study. The study concludes that the chronic dependence of donors not only affects the social aspect in light of the worsening indicators of poverty, privation and lack of protection, but also affected the identity of the public administration in the face of the continuous dismantling of the public sector and the imposition of priorities that respond to external bets more than meet national needs.